Extralinguistic Consultation in English–Chinese Translation: A Study Drawing on Eye-Tracking and Screen-Recording Data - Cui, Yixiao; Zheng, Binghan (Frontiers in Psychology, 2022)
Both linguistic and extralinguistic consultations are essential in translation practice and have been commonly investigated as an integral topic in previous studies. However, since extralinguistic information is usually longer in extent and not specifically designed for a linguistic purpose, extralinguistic consultations involve different search strategies compared with linguistic consultations. Drawing on eye-tracking and screen-recording data, this study compares linguistic and extralinguistic consultations in terms of cognitive resources allocation and information processing patterns in English–Chinese translation. It also explores the differences among 17 language learners, 20 student translators, and 21 professional translators, and the effect of extralinguistic consultation on their translation quality. The findings are as follows: (1) all participants allocate more attention and lower cognitive load to extralinguistic consultations than to linguistic consultations; (2) participants’ translation experience levels and their attention allocated to extralinguistic consultation show an inverted U-shaped relationship; and (3) participants who consult extralinguistic information before drafting or devote more attention to extralinguistic consultation produce target texts with significantly higher scores.